2021
DOI: 10.1155/2021/2270307
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Human Respiratory Syncytial Virus and Human Parainfluenza Virus Type 3 among Hospitalized Children in Northwest of Iran

Abstract: Background. Acute respiratory tract infections (ARTIs) are the leading cause of illnesses in children. Human respiratory syncytial virus (HRSV) and human parainfluenza viruses (HPIVs) are among the most common etiologic agents associated with viral respiratory tract infections in children worldwide. Nevertheless, limited information is available on the spread of infections of these two viruses in northwest Iran. Objective. The purpose of the current study is to evaluate the frequency of RSV and HPIV-3 and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…In a systematic review from the Middle East and North Africa (MENA) region, male infants within the first year of life were shown to be more susceptible to developing RSV infection. 30 In agreement with the results of this study, and consistent with similar findings reported from Iran, 3 , 31 here, we showed a possible preference for children to become infected with RSV and develop the symptoms of the disease during the age of infancy.…”
Section: Discussionsupporting
confidence: 93%
“…In a systematic review from the Middle East and North Africa (MENA) region, male infants within the first year of life were shown to be more susceptible to developing RSV infection. 30 In agreement with the results of this study, and consistent with similar findings reported from Iran, 3 , 31 here, we showed a possible preference for children to become infected with RSV and develop the symptoms of the disease during the age of infancy.…”
Section: Discussionsupporting
confidence: 93%
“…Years) and (64-70 Years), and the lowest one was (0%) at age group of (22)(23)(24)(25)(26)(27)(28) . which is in accordance with the studies reported from Iran In this study , Where they found most of those infected with the H1N1 virus were than less than 7 years , 64-70 Years .…”
Section: The Resultsmentioning
confidence: 91%
“…Influenza is contagious in people of all ages and is difficult to be assessed precisely since numerous, if not the majority, of those afflicted, do not require medical attention, and therefore, are not diagnosed (Aufi et al, 2021) .The results of present study revealed there are significant differences between the age groups and the percentage of HPIV3 positive patients with highest value was (2.70%) at both age group of (57-63 Years) and (64-70 Years). the lowest one was (0%) at age group of (22)(23)(24)(25)(26)(27)(28). I agree with who demonstrated that HPIV-3 seropositivity increase with age (Sale et al, 2010) .…”
Section: The Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…La alta tasa de infección sugiere una diseminación rápida. Puede causar enfermedad grave en lactantes como lo hace el VSR, pero esa gravedad disminuye a partir de los 3 años (Ramezannia et al, 2021). Es poco frecuente una enfermedad tan grave que requiera internación hospitalaria (Branche y Falsey, 2016).…”
Section: Infectividad De Los Virus Respiratoriosunclassified